Detection of Partial Discharge in Liquid via Interferometry - Liang Xue; Hao Zhou; Wenjing Wang; Junjie Chen; Lunming Qin; Chao Jiang; Haoyang Cui (IEEE Photonics Journal)
Partial discharge (PD) is the main cause of insulation breakdown in high voltage electrical equipment, which poses a potential threat to the safety and reliability of equipment. Traditional PD detection methods have limitations in liquid insulation systems. In this paper, an interferometric method for detecting PD in liquid is proposed. Through the experimental platform based on the Michelson interference method, the PD in the water sample is excited by the voltage applied by the lightning surge generator, and the interference fringes distorted are collected by the CCD camera. The experimental results show that the peak value of the phase distribution recovered from interferogram increases when the voltage increases. In addition, when the liquid contains particles that degrade the insulation properties, the effect on the insulation properties can be judged according to the interferometry. This study verifies the feasibility and effectiveness of PD detection in liquid based on Michelson interferometry, and provides a new idea for condition monitoring and fault diagnosis of liquid insulation system.